Continuous monitoring of fetal heart rate and uterus contractions - P.Thirupathinaidu, S. Roji Marjorie (International Journal of Advanced Science and Technology, 2020)
During pregnancy, fetal heart rate monitoring plays a vital role to find the health status of fetal. In this paper, a survey is done on the devices and the methods which are used for fetal heart rate monitoring. And a new device is proposed for fetal heart rate monitoring and uterine contraction. This device consists of a fetal digital stethoscope sensor and an EMG sensor. A microcontroller (Arduino AT Mega 328 UNO) helps to fetch signals and to obtain clear data. The accurate fetal heart rate can be sent as a text to the respective consultant through mobile phone by the usage of GSM. The analog view of the uterine contraction and fetal heart rate can be simulated on the desktop. This is very flexible and low-cost device that helps the patient to monitor the fetal heart rate at home.